Radar Signal Processing Method of Space-Time-Frequency Focus-Before-Detects - Xu Jia; Peng Ying-ning; Xia Xiang-gen; Long Teng; Mao Er-ke (Leida xuebao, 2014)
For the high-speed, high-maneuverability and stealthy target detection via modern radar in complicated electromagnetic environment, a novel radar signal processing approach called Space-Time-Frequency Focus-Before-Detection (STF-FBD) via multi-dimensional coherent integration is proposed. Based on space-timefrequency signal modeling for modern radar systems, the proposed method can effectively suppress the strong interference, such as clutter and active jamming, and overcome the problems of scaled effect of high-speed targets, aperture fill time, sparse frequency sub-band synthesis, across range units, across Doppler units and across beam units. The proposed methods improves radar signal processing performance on the steps like energy integration, target detection, parameter estimation, maneuver tracking, feature extraction and target recognition. It also outperforms the existing Track-Before-Detection (TBD) methods and establish a unified STF-FBD and STF-FBD-TBD radar signal processing frame work. The proposed method is suitable for high-speed, high-maneuverability and stealthy target, as well as for conventional targets. It is applicable for new-generation modern radar, as well as for conventional radars, and may find application to different field.